PELATIHAN PENGELOLAAN LINGKUNGAN PERAIRAN WADUK PENJALIN: DUKUNGAN BAGI KESEIMBANGAN EKOSISTEM DAN PENINGKATAN EKONOMI MASYARAKAT - Hidayati, Nuning Vita; Muslih, Muslih; Soedibya, Petrus Hary Tjahja; Fikriyya, Nabela; Hastuti, Dewi Wisudyanti Budi; Tohir, Tohir; Riviani, Riviani; Putri, Adinda Kurnia; Raharja, Ferry Cahya; Hidayatullah, Irwan; Putri, Desta Fatma; Wibowo, Mahbub Fuad (Jurnal Abdi Insani, 2025)
One of the reservoirs in Central Java is Penjalin Reservoir, which is specifically situated in Winduaji Village, Paguyangan District, Brebes Regency. Penjalin Reservoir is now dealing with environmental degradation issues, such as highly filthy water and rapidly growing water algae that might upset the ecosystem's equilibrium. The Jenderal Soedirman University (UNSOED) Team and the local Village Government, working through the Village Community Empowerment Institution (LPMD), followed up on this by developing a program of activities to combat environmental degradation in order to preserve the ecosystem's equilibrium and generate income for the neighborhood. Socialization and training for this program were conducted as a first stage. Technical advice for fish farming operations, including seed certification and business management training, will also be provided. Efforts are also being made to reintroduce fish, particularly herbivorous fish species, in an attempt to quickly overcome hydrilla. Facilities for consultation are offered as a crucial component of carrying out this activity. The first stage, socialization and training targeted at the people living near the Penjalin Reservoir, is the main topic of this essay. Educating the community about the current state of the Penjalin Reservoir and the significance of maintaining the aquatic ecosystem's equilibrium is the top goal during the socialization stage. In addition to talking about environmental issues, this program also covers the financial benefits of managing the Penjalin Reservoir sustainably, such as by raising carp and tilapia, which both benefit the ecosystem and boost revenue. Participants are encouraged to comprehend the training's goal of preserving the ecology and boosting the local economy by highlighting the significance of the community's active participation in improvements to the reservoir. The execution of the following work stage depends on this task. An excellent partner that may support and act as a stimulant for the local population is LPMD, an official village-level organization. A participatory strategy is used to carry out the programs, meaning that program partners actively participate in every activity.